Leptin Receptor Deficiency Protects Mice against Chronic Cerebral Hypoperfusion-Induced Neuroinflammation and White Matter Lesions - Yu Du; Yufei Song; Xiaojie Zhang; Yan Luo; Wenying Zou; Jiawei Zhang; Jianliang Fu (Mediators of Inflammation)
Leptin participates in the inflammatory responses in multiple cell types and animal models. Chronic cerebral hypoperfusion (CCH) induces inflammation in the central nervous system (CNS), which acts as one of the main reasons for CCH-induced white matter lesions (WMLs). But whether leptin participates in the pathogenesis of CCH-induced WMLs remains unknown. Therefore, we performed bilateral common carotid artery stenosis (BCAS) to induce CCH on the leptin receptor- (LepR-) deficient db/db mice, aiming to evaluate the possible involvement of leptin in CCH-induced cognitive impairment, WMLs, and neuroinflammation, and further explore the effect of leptin on chronic hypoxia-induced inflammation using the BV2 microglial cell line. After four weeks of BCAS, wild-type mice showed significant working memory deficits, WMLs, activation of microglia and astrocytes, decrease in the number of oligodendrocytes, downregulation of myelin basic protein expression, and increase in the expression of TNF-α and IL-1β; however, four weeks of BCAS failed to induce significant changes in the LepR-deficient db/db mice but elevated the production of anti-inflammatory cytokines and activated the M2 microglia. We further confirmed that leptin would aggravate the hypoxia-induced proinflammatory cytokine expression in the BV2 microglia cell line. These results suggested that LepR deficiency would protect mice against the CCH-induced cognitive impairment and WMLs by inhibiting glial activation and suppressing proinflammatory responses as well as promoting anti-inflammatory cytokine expression and M2 microglia activation in the white matter.